Hydrogel-based 3D human iPSC-derived neuronal culture for the study of rabies virus infection - Muangsanit, Papon; Chailangkarn, Thanathom; Tanwattana, Nathiphat; Wongwanakul, Ratjika; Lekcharoensuk, Porntippa; Kaewborisuth, Challika (Frontiers in Cellular and Infection Microbiology, 2023)
Background Rabies is a highly fatal infectious disease that poses a significant threat to human health in developing countries. In vitro study-based understanding of pathogenesis and tropism of different strains of rabies virus (RABV) in the central nervous system (CNS) is limited due to the lack of suitable culture models that recapitulate the complex communication pathways among host cells, extracellular matrices, and viruses. Therefore, a three-dimensional (3D) cell culture that mimics cell-matrix interactions, resembling in vivo microenvironment, is necessary to discover relevant underlying mechanisms of RABV infection and host responses. Methods The 3D collagen-Matrigel hydrogel encapsulating hiPSC-derived neurons for RABV infection was developed and characterized based on cell viability, morphology, and gene expression analysis of neuronal markers. The replication kinetics of two different strains of RABV [wild-type Thai (TH) and Challenge Virus Standard (CVS)-11 strains] in both 2D and 3D neuronal cultures were examined. Differential gene expression analysis (DEG) of the neuropathological pathway of RABV-infected 2D and 3D models was also investigated via NanoString analysis. Results The 3D hiPSC-derived neurons revealed a more physiologically interconnected neuronal network as well as more robust and prolonged maturation and differentiation than the conventional 2D monolayer model. TH and CVS-11 exhibited distinct growth kinetics in 3D neuronal model. Additionally, gene expression analysis of the neuropathological pathway observed during RABV infection demonstrated a vast number of differentially expressed genes (DEGs) in 3D model. Unlike 2D neuronal model, 3D model displayed more pronounced cellular responses upon infection with CVS-11 when compared to the TH-infected group, highlighting the influence of the cell environment on RABV-host interactions. Gene ontology (GO) enrichment of DEGs in the infected 3D neuronal culture showed alterations of genes associated with the inflammatory response, apoptotic signaling pathway, glutamatergic synapse, and trans-synaptic signaling which did not significantly change in 2D culture. Conclusion We demonstrated the use of a hydrogel-based 3D hiPSC-derived neuronal model, a highly promising technology, to study RABV infection in a more physiological environment, which will broaden our understanding of RABV-host interactions in the CNS.